Biochemical and cultural characteristics of "JK" coryneforms. Issue 6 (June 1986) - Bayston, R; Higgins, J
Abstract : Antibiotic resistant coryneforms (group JK) have increasingly been reported as causes of serious sepsis in the immunosuppressed and in patients with implants. Their cultural and biochemical characteristics were examined in an attempt to provide a simple scheme for their recognition in the clinical laboratory. Their susceptibilities to a range of antimicrobials were determined, and an enriched selective medium was developed for their isolation from normally non-sterile sites. The JK coryneforms fell into a fairly homogeneous group, producing colonial morphology and biochemical profiles identical with reference strains, which allowed their recognition and differentiation from other coryneforms. All strains were resistant to penicillin and susceptible to vancomycin, but there was considerable variation with respect to other antimicrobials. There is scope for further rationalisation of biochemical tests for the recognition of these organisms.